Lithium battery positive electrode material and preparation method thereof

By introducing tantalum elements into the positive electrode material of lithium battery and designing a calcination temperature curve, a three-layer structure is formed, which solves the problems of insufficient energy density and reduced circulation capacity of lithium battery, and significantly improves the cycling performance and stability of the battery.

CN119230788AActive Publication Date: 2024-12-31BEIJING INST OF TECH
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411457629.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2024-12-31
Estimated Expiration
2044-10-18

AI Technical Summary

Technical Problem

The energy density of lithium batteries is insufficient, resulting in a rapid decrease in capacity during the cycle, which is unable to meet market demand, and increasing the upper voltage limit will affect battery stability.

Method used

The lithium battery positive electrode material adopts a three-layer structure, including an ordered layered body, a surface gradient disordered structure layer and a transition layer, forms a uniformly covered surface by introducing tantalum elements and controlling the preparation process, especially the temperature curve design of the calcination treatment. Gradient disordered layers improve the high-pressure stability of the material.

Benefits of technology

It effectively improves the performance of the positive electrode material of lithium battery, enhances ionic conductivity, inhibits the contact between the electrode material and the electrolyte and oxygen precipitation, protects the lattice structure, and extends the cycle life and capacity retention rate of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119230788A_ABST
    Figure CN119230788A_ABST
Patent Text Reader

Abstract

The invention provides a lithium battery positive electrode material. The positive electrode material comprises an ordered layered main body, a surface gradient disordered structure layer and a transition layer positioned between the ordered layered main body and the surface gradient disordered structure layer. The first thickness of the surface gradient disordered structure layer is within a first preset thickness range, and the second thickness of the transition layer is within a second preset thickness range. The invention further provides a preparation method of the lithium battery positive electrode material, the preparation method comprises the following steps: respectively adding lithium acetate and absolute ethyl alcohol as well as tantalum ethoxide and absolute ethyl alcohol into a first container and a second container, and the mass ratio of tantalum ethoxide to lithium acetate is within a preset proportion range; dropwise adding the solution in the second container into the solution in the first container to form a mixed solution; adding lithium cobalt oxide into the mixed solution, and carrying out stirring and drying treatment to form a dried substance; and calcining the dried product to obtain the positive electrode material, and calcining by adopting a preset temperature curve.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of lithium battery technology, and in particular to a lithium battery positive electrode material and a preparation method thereof. Background Art

[0002] With the rapid development of new energy vehicles in recent years and the increasing global attention to sustainable development, the research and application of energy storage materials have become a hot topic. Among the many energy storage technologies, lithium-ion batteries (LIBs) have attracted much attention due to their high energy density, long life and high efficiency, and have become the core of the clean technology revolution. In the past decade, the global production of lithium-ion batteries has increased rapidly, but the energy density of lithium-ion batteries is not high enough and is far from meeting market demand. In order to increase the capacity, it is an idea to extract more lithium by increasing the upper voltage limit, but this usually causes the battery capacity to decrease rapidly with the cycle. Therefore, it is necessary to provide a lithium battery positive electrode material and a preparation method thereof to improve the high-voltage stability of the positive electrode material, thereby effectively improving the capacity and performance of the lithium battery. Summary of the invention

[0003] An embodiment of the present specification provides a positive electrode material for a lithium battery, the positive electrode material comprising: an ordered layered main body; a surface gradient disordered structure layer, wherein the first thickness of the surface gradient disordered layer is within a first preset thickness range; and a transition layer, wherein the transition layer is located between the ordered layered main body and the surface gradient disordered structure layer, and the second thickness of the transition layer is within a second preset thickness range.

[0004] In some embodiments, the surface gradient disordered structure layer is formed by auxiliary element preparation, and the auxiliary element includes Ta element.

[0005] In some embodiments, the first preset thickness ranges from 4 nm to 20 nm.

[0006] In some embodiments, the first preset thickness ranges from 4 nm to 15 nm.

[0007] In some embodiments, the first preset thickness ranges from 5 nm to 10 nm.

[0008] In some embodiments, the second preset thickness ranges from 5 nm to 15 nm.

[0009] In some embodiments, the second preset thickness ranges from 6 nm to 12 nm.

[0010] In some embodiments, the second preset thickness range is 6-8 nm.

[0011] The embodiments of the present specification also provide a method for preparing a positive electrode material for a lithium battery. The positive electrode material comprises: adding lithium acetate and anhydrous ethanol and tantalum ethanol and anhydrous ethanol to a first container and a second container, respectively, wherein the mass ratio of the tantalum ethanol to the lithium acetate is within a preset ratio range; dropping the solution in the second container into the solution in the first container to form a mixed solution; adding lithium cobalt oxide to the mixed solution, stirring and drying the mixed solution to form a dried product; calcining the dried product to obtain the positive electrode material, wherein the calcination adopts a preset temperature curve.

[0012] In some embodiments, the preset temperature curve includes at least a temperature increase phase and a temperature decrease phase, and the temperature increase phase is substantially symmetrical to the temperature decrease phase.

[0013] In the embodiments of this specification, by introducing auxiliary elements (e.g., tantalum) during the preparation of the positive electrode material, and controlling the preparation process (e.g., designing the temperature curve during the calcination process), the prepared positive electrode material presents a three-layer structure (ordered layered main body + transition layer + surface gradient disordered layer). The surface gradient disordered layer is uniformly covered on the surface of the positive electrode material, which can not only provide excellent ionic conductivity, but also inhibit the contact between the ordered structure inside the electrode material and the electrolyte, prevent surface side reactions and the precipitation of oxygen, and thus protect the fragile lattice on the surface of the positive electrode material, effectively improving the performance of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] This specification will be further described in the form of exemplary embodiments, which will be described in detail by the accompanying drawings. These embodiments are not restrictive, and in these embodiments, the same number represents the same structure, wherein:

[0015] Figure 1 is a flow chart of an exemplary method for preparing a positive electrode material for a lithium battery according to some embodiments of this specification.

[0016] Figure 2 It is a schematic diagram of the structure of an exemplary lithium battery positive electrode material according to some embodiments of this specification.

[0017] Figure 3 is a morphological image of an exemplary positive electrode material according to some embodiments of the present specification.

[0018] Figure 4 is a structural morphology image of an exemplary positive electrode material according to some embodiments of the present specification.

[0019] Figure 5 These are the cycle performance test results of the exemplary positive electrode materials and ordinary lithium cobalt oxide positive electrode materials shown in some embodiments of this specification.

[0020] Figure 6 It is a structural morphology image of the exemplary positive electrode material after cycle testing according to some embodiments of this specification.

[0021] Figure 7 This is the structural morphology image of ordinary lithium cobalt oxide positive electrode material after cycle testing.

[0022] Figure 8 is a morphological image of the exemplary positive electrode material after cycle testing according to some embodiments of this specification. DETAILED DESCRIPTION

[0023] In order to more clearly illustrate the technical solutions of the embodiments of this specification, the following is a brief introduction to the drawings required for the description of the embodiments. Obviously, the drawings described below are only some examples or embodiments of this specification. For ordinary technicians in this field, this specification can also be applied to other similar scenarios based on these drawings without creative work. Unless it is obvious from the language environment or otherwise explained, the same reference numerals in the figures represent the same structure or operation.

[0024] It should be understood that the "system", "device", "unit" and / or "module" used herein are a method for distinguishing different components, elements, parts, portions or assemblies at different levels. However, if other words can achieve the same purpose, the words can be replaced by other expressions.

[0025] As shown in this specification and claims, unless the context clearly indicates an exception, the words "a", "an", "an" and / or "the" do not refer to the singular and may also include the plural. Generally speaking, the terms "comprise" and "include" only indicate the inclusion of the steps and elements that have been clearly identified, and these steps and elements do not constitute an exclusive list. The method or device may also include other steps or elements.

[0026] Flowcharts are used in this specification to illustrate the operations performed by the system according to the embodiments of this specification. It should be understood that the preceding or following operations are not necessarily performed precisely in order. Instead, the steps may be processed in reverse order or simultaneously. At the same time, other operations may also be added to these processes, or one or more operations may be removed from these processes.

[0027] Figure 1This is an exemplary method for preparing positive electrode materials for lithium batteries according to some embodiments of this specification. In some embodiments, process 100 can be automatically executed by a control system. For example, process 100 can be implemented by control instructions, and the control system controls each component to complete each operation of process 100 based on the control instructions. In some embodiments, process 100 can be semi-automatically executed. For example, one or more operations of process 100 can be manually performed by an operator. In some embodiments, when completing process 100, one or more additional operations not described can be added, and / or one or more operations discussed herein can be deleted. In addition, Figure 1 The order of operations shown in is not limiting. Figure 1 As shown, process 100 may include the following steps.

[0028] Step 110: Add lithium acetate and anhydrous ethanol and tantalum ethoxide and anhydrous ethanol into the first container and the second container respectively.

[0029] In some embodiments, the first container and the second container can be centrifuge tubes, glass sample bottles (eg, screw-mouth bottles), etc. In some embodiments, lithium acetate and tantalum ethoxide can both be powdered or granular raw materials, and anhydrous ethanol is used as a solvent.

[0030] In some embodiments, anhydrous ethanol may be added to both the first container and the second container, and then lithium acetate and tantalum ethoxide may be added respectively. In some embodiments, in order to ensure the stability of the preparation process, the process of adding the above raw materials to the first container and the second container is carried out under a protective atmosphere (e.g., an argon atmosphere).

[0031] In some embodiments, the mass ratio of tantalum ethoxide to lithium acetate is within a preset ratio range. In some embodiments, the preset ratio range is 1.2:1 to 2.2:1. In some embodiments, the preset ratio range is 1.1:1 to 2.1:1. In some embodiments, the preset ratio range is 1.05:1 to 2:1. By setting a suitable mass ratio of tantalum ethoxide to lithium acetate, subsequent reactions proceed normally and side reactions and by-products are avoided as much as possible.

[0032] Step 120, dripping the solution in the second container into the solution in the first container.

[0033] In some embodiments, before the solution in the second container is dripped into the solution in the first container, the first container and the second container are sealed (for example, sealed with a sealing film) and placed in a protective atmosphere (for example, an argon atmosphere), and the solutions in the two containers are stirred. For example, a magnetic stirrer can be used to stir for a preset time (for example, 2 hours) until the raw material is fully dissolved in the solvent (anhydrous ethanol). In some embodiments, during the stirring process, the temperature is lowered so that the solution temperature is at a relatively low temperature (for example, 0-10° C.) to prevent tantalum ethoxide from decomposing at high temperatures.

[0034] In some embodiments, after the solutions in the two containers are fully stirred, the solution in the second container (i.e., a solution of tantalum ethoxide dissolved in anhydrous ethanol) is dripped dropwise into the solution in the first container (i.e., a solution of lithium acetate dissolved in anhydrous ethanol). During the dripping process, the first container is continuously shaken or the solution in the first container is continuously stirred so that the dripped solutions can be fully mixed.

[0035] In some embodiments, after the solution in the second container is dripped into the first container, the mixed solution is fully stirred again to further ensure that the solution is evenly mixed. In some embodiments, the mixed solution can be fully stirred until a sol is formed. For example, a magnetic stirrer can be used to stir for a preset time (e.g., 2 hours) until the Tyndall effect appears (indicating the formation of a sol). In some embodiments, during the stirring process, a cooling treatment is performed so that the solution temperature is at a relatively low temperature (e.g., 0-10°C) to prevent tantalum ethoxide from decomposing at high temperatures.

[0036] Step 130, adding lithium cobalt oxide to the above solution, stirring and drying the solution to form a dried product.

[0037] In some embodiments, as described above, after the solutions in the two containers are fully mixed, lithium cobaltate (e.g., lithium cobaltate powder or particles) is added to the above solution. In some embodiments, the mass ratio of the added lithium cobaltate to tantalum ethoxide is within a preset range. In some embodiments, the preset range is 100:1 to 180:1. In some embodiments, the mass ratio of the added lithium cobaltate to tantalum ethoxide is within a preset range. In some embodiments, the preset range is 100:1 to 150:1. In some embodiments, the mass ratio of the added lithium cobaltate to tantalum ethoxide is within a preset range. In some embodiments, the preset range is 120:1 to 140:1. By setting the mass ratio of lithium cobaltate to tantalum ethoxide, subsequent reactions proceed normally and side reactions and by-products are avoided as much as possible.

[0038] In some embodiments, after adding lithium cobalt oxide, stirring treatment is performed (for example, stirring for 12 hours using a magnetic stirrer). The stirring treatment allows lithium acetate and tantalum ethoxide to evenly wrap the lithium cobalt oxide particles. After sufficient stirring, drying treatment is performed. For example, it can be dried at a certain temperature above room temperature (for example, 70-100°C) for 2-6 hours). In some embodiments, the drying treatment is performed under a vacuum environment. In some embodiments, the drying treatment is performed under a protective atmosphere (for example, an argon atmosphere).

[0039] Step 140, calcining the dried product to obtain a positive electrode material.

[0040] In some embodiments, after the drying process is completed to obtain a dried product, the dried product is ground to obtain a relatively fine particle powder. Further, the powder is calcined to prepare a lithium battery positive electrode material. In some embodiments, the calcination process is performed in an atmosphere containing oxygen.

[0041] In some embodiments, the calcination process adopts a preset temperature curve. The preset temperature curve includes at least a heating stage and a cooling stage. In some embodiments, the heating stage and the cooling stage are substantially symmetrical. In some embodiments, the heating stage includes a first heating stage and a second heating stage, and the cooling stage includes a first cooling stage and a second cooling stage. In some embodiments, the first heating stage is relatively uniform heating, and the second heating stage is variable speed heating; the first cooling stage is variable speed cooling, and the second cooling stage is relatively uniform cooling. In some embodiments, the first heating stage is substantially symmetrical with the second cooling stage, and the second heating stage is substantially symmetrical with the first cooling stage. In some embodiments, the heating rate and / or the cooling rate can be designed in combination with actual needs. By designing a reasonable and appropriate temperature curve, a multilayer structure is formed on the surface of the finally prepared positive electrode material (to be described in detail below), thereby improving the performance of the positive electrode material.

[0042] As an example only, assuming that the initial temperature is 25°C, the preset temperature curve is as shown in formula (1):

[0043] Wherein, T represents the real-time temperature during the calcination process, t represents time, a, b, c, d, e, and f are temperature setting parameters related to the calcination process, and t1, t2, and t3 are time nodes during the calcination process. Specifically, the heating rate a in the first heating stage and the cooling rate e in the second cooling stage can be substantially the same, and the curves of the two stages are basically symmetrical. The second heating stage is variable speed heating, and the first cooling stage is variable speed cooling, and the curves of the two stages are basically symmetrical.

[0044] As a specific example, assuming that the initial temperature is 25°C, the preset temperature curve is shown in formula (2): Wherein, T represents the real-time temperature during the calcination process, and t represents the time. Through this temperature curve, the temperature can be uniformly and stably raised from the initial temperature (25°C) to 800°C (heating rate 5°C / second), and then the heating rate is fast and then slow, and the temperature rises to 1000°C. Further, the cooling stage begins, and the cooling rate is slow and then fast, and the temperature will reach 800°C. Finally, the temperature is uniformly and stably cooled to the initial temperature (cooling rate 5°C / second).

[0045] During the calcination process, acetate and ethanoic acid ions decompose, and due to the wrapping effect of lithium acetate and tantalum ethoxide on the lithium cobalt oxide particles, the elements are mixed to a certain extent (for example, trace amounts of Ta elements and Co elements are mixed to a certain extent, and Co elements and Li elements are mixed to a certain extent), forming a multilayer structure with a surface gradient disorder (to be described in detail below).

[0001] In some embodiments, the positive electrode material prepared by the above preparation method is a multilayer structure, including an ordered layered main body, a surface gradient disordered structure layer and a transition layer. Specifically, the ordered layered main body is a lithium cobalt oxide matrix, and in the surface gradient disordered structure layer, the tantalum element randomly occupies part of the position originally occupied by the cobalt element, and the cobalt element randomly occupies part of the position originally occupied by the lithium element, forming a surface gradient disordered state as a whole, and the transition layer is a transition region where the ordered structure changes to the disordered structure. A specific description of the electrode material structure can be found below.

[0002] By introducing tantalum elements (the tantalum ethoxide mentioned above) during the preparation of the positive electrode material, and controlling the preparation process (especially the design of the temperature curve of the calcination process mentioned above), the prepared positive electrode material presents a three-layer structure (ordered layered main body + transition layer + surface gradient disordered layer). The surface gradient disordered layer is evenly covered on the surface of the positive electrode material, which can not only provide excellent ionic conductivity, but also inhibit the contact between the ordered structure inside the electrode material and the electrolyte, prevent surface side reactions and the precipitation of oxygen, and thus protect the fragile lattice on the surface of the positive electrode material and improve the performance of the positive electrode material.

[0003] In some embodiments, after the positive electrode material is prepared, process 100 may further include a process of processing the electrode sheet.

[0004] Step 150 , mixing the positive electrode material with the conductive carbon black and PVDF in a preset ratio, and grinding the mixture.

[0005] In some embodiments, the positive electrode material may be ground before mixing to make subsequent mixing more complete. In some embodiments, the mixing ratio of the positive electrode material to the conductive carbon black and PVDF is 8:1:1 or 7:2:1, which can be designed in combination with actual needs to ensure that the amount of active material is much higher than other substances. In some embodiments, when mixing, a certain amount of NMP solution is added so that the positive electrode material, conductive carbon black and PVDF can be more fully dissolved and mixed, which is helpful for subsequent coating treatment.

[0006] Step 160 , coating the ground mixture on an electrode substrate and drying it to obtain a positive electrode sheet.

[0007] It should be noted that the above description of the process 100 is only for example and illustration, and does not limit the scope of application of the present application. For those skilled in the art, various modifications and changes can be made to the process 100 under the guidance of the present application. However, these modifications and changes are still within the scope of the present application.

[0008] Figure 2 Schematic diagram of the structure of an exemplary lithium battery positive electrode material according to some embodiments of this specification. Figure 2 As shown, the positive electrode material includes an ordered layered main body, a surface gradient disordered structure layer and a transition layer.

[0009] The ordered layered main body is the electrode material matrix. For example, taking lithium cobalt oxide electrode as an example, the ordered layered main body is the ordered structure of lithium cobalt oxide.

[0010] The surface gradient disordered structure layer is a disordered structure layer covering the outside of the substrate. By introducing specific auxiliary elements (such as tantalum elements) and setting the preparation process (such as calcination treatment temperature curve design), a surface gradient disordered structure layer is introduced to cover the surface of the substrate, thereby improving the reaction process of the electrode material in the battery reaction and improving the performance of the electrode material. For example, still taking the lithium cobalt oxide electrode as an example, the ordered layered main body is the lithium cobalt oxide ordered structure. By introducing tantalum elements during the electrode preparation process and specifically designing the preparation process, a surface gradient disordered structure is introduced on the surface of the lithium cobalt oxide ordered structure. In this disordered structure, the tantalum element randomly replaces part of the cobalt element, and the cobalt element randomly replaces part of the lithium element, forming a gradient disordered structure.

[0011] The transition layer is located between the ordered layered main body and the surface gradient disordered structure, showing a transition state. For example, taking the lithium cobalt oxide battery as an example, in the transition layer, a small amount of cobalt element occupies the position of lithium element.

[0012] In some embodiments, in order to ensure the performance of the electrode material, the thickness of the surface gradient disordered layer and the transition layer must meet the requirements. For the surface gradient disordered layer, if the thickness is too large, it will affect the lithium ion embedding kinetics of the lithium battery; on the contrary, if the thickness is too small, it will not be able to effectively protect the internal ordered layered structure, and it will be difficult to avoid the contact between the internal ordered layered structure and the electrolyte. For the transition layer, if the thickness is too large, it will not only affect the lithium ion embedding kinetics of the lithium battery, but also affect the element arrangement and thickness design of the gradient disordered layer; on the contrary, if the thickness is too small, it will not only be unable to effectively avoid the contact between the internal ordered layered structure and the electrolyte, but also be unable to achieve stable continuity between the ordered layered body and the surface gradient disordered structure.

[0013] In some embodiments, the first thickness of the surface gradient disordered layer is within a first preset thickness range. In some embodiments, the first preset thickness range is 4-20 nm. In some embodiments, the first preset thickness range is 4-15 nm. In some embodiments, the first preset thickness range is 5-12 nm. In some embodiments, the first preset thickness range is 5-10 nm.

[0014] In some embodiments, the second thickness of the transition layer is within a second preset thickness range. In some embodiments, the second preset thickness range is 5-15 nm. In some embodiments, the second preset thickness range is 6-12 nm. In some embodiments, the second preset thickness range is 6-10 nm. In some embodiments, the second preset thickness range is 6-8 nm. Example 1

[0015] In a glove box with an argon atmosphere, add 2 ml and 1 ml of anhydrous ethanol to container 1 and container 2, respectively. Subsequently, add 16 mg of lithium acetate and 20 ul of tantalum ethoxide to container 1 and container 2, respectively, and perform magnetic stirring at low temperature for 2 hours. This process is always carried out in an argon atmosphere. After the stirring is completed, the liquid in container 2 is dripped into container 1 drop by drop, and the container is stirred continuously. The resulting solution is stirred for 2 hours until the solution shows the Tyndall effect. Use ice cubes for intermittent cooling during stirring to ensure that the temperature of the solution is between 0-10 degrees Celsius.

[0016] 6 g of lithium cobalt oxide was added to the above solution and stirred for 10 hours. The obtained mixture was dried in a vacuum drying oven at 75 degrees Celsius for 10 hours, and then the obtained powder was ground and calcined. The calcination atmosphere was oxygen. The temperature change rate in the heating and cooling stages was 5 degrees Celsius per minute. The high-temperature calcination stage lasted for 120 minutes. The temperature fluctuated between 800 and 1000 degrees Celsius, first rising from 800 degrees to 1000 degrees more and more slowly, and then falling from 1000 degrees to 800 degrees more and more quickly. The curve of temperature change over time is described by the above formula (2).

[0017] The positive electrode material is obtained by grinding the powder obtained in the previous step. The morphology picture taken by scanning electron microscope is as follows: Figure 3 shown.

[0018] The surface area of ​​the cathode material was extracted using a FIB dual-beam electron microscope, and atomic-level imaging was performed using a double spherical aberration-corrected transmission electron microscope, such as Figure 4 As shown, the surface area of ​​the prepared positive electrode material particles transitions from an ordered state to a disordered state from the inside to the outside. Zone I is the surface layer, which is in a gradient disordered state (disordered rock salt phase); Zone II is the intermediate transition layer, which is in a transitional state (spinel phase), and Zone III is an ordered layered area. The thickness of the gradient disordered layer on the surface of Zone I is about 10nm.

[0019] Furthermore, the prepared positive electrode material was coated on aluminum foil, and the liquid battery was assembled in the order of positive electrode shell-positive electrode sheet-diaphragm-electrolyte-lithium sheet-gasket-spring-negative electrode shell, and the long cycle performance of the assembled battery was tested under 4.6V 0.5C conditions using a battery testing system. Figure 5 As shown, the prepared positive electrode material can retain 73% of the discharge capacity after 500 cycles, while the ordinary lithium cobalt oxide sample has only 53% of the remaining capacity. The positive electrode material prepared in this embodiment can effectively improve the performance of the positive electrode material, thereby improving the battery performance.

[0020] Furthermore, the samples after cycling were observed using transmission electron microscopy, e.g. Figure 6 , Figure 7 As shown, it can be seen that the surface of the ordinary lithium cobalt oxide sample has obvious lattice breakage and bending of the surface cobalt oxide layer, while the surface of the sample prepared in this embodiment shows a disordered rock salt phase and the crystal structure is well preserved.

[0021] Furthermore, the samples after 200 cycles were observed using a scanning electron microscope, such as Figure 8 As shown, it can also be clearly seen that the sample prepared in this embodiment retains a relatively complete morphology, and there is no layer slippage or particle breakage.

[0022] The beneficial effects that may be brought about by the embodiments of the present application include but are not limited to: by introducing auxiliary elements (e.g., tantalum elements) during the preparation of the positive electrode material, and controlling the preparation process (e.g., designing the temperature curve during the calcination process), the prepared positive electrode material presents a three-layer structure (ordered layered main body + transition layer + surface gradient disordered layer). The surface gradient disordered layer is evenly covered on the surface of the positive electrode material, which can not only provide excellent ionic conductivity, but also inhibit the contact between the ordered structure inside the electrode material and the electrolyte, prevent surface side reactions and the precipitation of oxygen, and then protect the fragile lattice on the surface of the positive electrode material, effectively improving the performance of the positive electrode material.

[0023] It should be noted that different embodiments may produce different beneficial effects. In different embodiments, the beneficial effects that may be produced may be any one or a combination of the above, or any other beneficial effects that may be obtained.

[0024] The basic concepts have been described above. Obviously, for those skilled in the art, the above detailed disclosure is only for example and does not constitute a limitation of this specification. Although not explicitly stated here, those skilled in the art may make various modifications, improvements and corrections to this specification. Such modifications, improvements and corrections are suggested in this specification, so such modifications, improvements and corrections still belong to the spirit and scope of the exemplary embodiments of this specification.

[0025] At the same time, this specification uses specific words to describe the embodiments of this specification. For example, "one embodiment", "an embodiment", and / or "some embodiments" refer to a certain feature, structure or characteristic related to at least one embodiment of this specification. Therefore, it should be emphasized and noted that "one embodiment" or "an embodiment" or "an alternative embodiment" mentioned twice or more in different positions in this specification does not necessarily refer to the same embodiment. In addition, certain features, structures or characteristics in one or more embodiments of this specification can be appropriately combined.

[0026] In addition, unless explicitly stated in the claims, the order of the processing elements and sequences described in this specification, the use of alphanumeric characters, or the use of other names are not intended to limit the order of the processes and methods of this specification. Although the above disclosure discusses some invention embodiments that are currently considered useful through various examples, it should be understood that such details are only for illustrative purposes, and the attached claims are not limited to the disclosed embodiments. On the contrary, the claims are intended to cover all modifications and equivalent combinations that are consistent with the essence and scope of the embodiments of this specification. For example, although the system components described above can be implemented by hardware devices, they can also be implemented only by software solutions, such as installing the described system on an existing server or mobile device.

[0027] Similarly, it should be noted that in order to simplify the description disclosed in this specification and thus help understand one or more embodiments of the invention, in the above description of the embodiments of this specification, multiple features are sometimes combined into one embodiment, figure or description thereof. However, this disclosure method does not mean that the features required by the subject matter of this specification are more than the features mentioned in the claims. In fact, the features of the embodiments are less than all the features of the single embodiment disclosed above.

[0028] In some embodiments, numbers describing the number of components and attributes are used. It should be understood that such numbers used in the description of the embodiments are modified by the modifiers "about", "approximately" or "substantially" in some examples. Unless otherwise specified, "about", "approximately" or "substantially" indicate that the numbers are allowed to vary by ±20%. Accordingly, in some embodiments, the numerical parameters used in the specification and claims are approximate values, which may change according to the required features of individual embodiments. In some embodiments, the numerical parameters should take into account the specified significant digits and adopt the general method of retaining digits. Although the numerical domains and parameters used to confirm the breadth of their range in some embodiments of this specification are approximate values, in specific embodiments, the setting of such numerical values ​​is as accurate as possible within the feasible range.

[0029] Each patent, patent application, patent application publication, and other materials, such as articles, books, specifications, publications, documents, etc., cited in this specification are hereby incorporated by reference in their entirety. Except for application history documents that are inconsistent with or conflicting with the contents of this specification, documents that limit the broadest scope of the claims of this specification (currently or later attached to this specification) are also excluded. It should be noted that if the descriptions, definitions, and / or use of terms in the materials attached to this specification are inconsistent or conflicting with the contents described in this specification, the descriptions, definitions, and / or use of terms in this specification shall prevail.

[0030] Finally, it should be understood that the embodiments described in this specification are only used to illustrate the principles of the embodiments of this specification. Other variations may also fall within the scope of this specification. Therefore, as an example and not a limitation, alternative configurations of the embodiments of this specification may be considered consistent with the teachings of this specification. Accordingly, the embodiments of this specification are not limited to the embodiments explicitly introduced and described in this specification.

Claims

1. A positive electrode material for a lithium battery, characterized in that: The positive electrode material comprises: Ordered layered host; A surface gradient disordered structure layer, wherein a first thickness of the surface gradient disordered structure layer is within a first preset thickness range; A transition layer is located between the ordered layered body and the surface gradient disordered structure layer, and the second thickness of the transition layer is within a second preset thickness range.

2. The positive electrode material according to claim 1, characterized in that The surface gradient disordered structure layer is formed by auxiliary element preparation, and the auxiliary element includes Ta element.

3. The positive electrode material according to claim 1, characterized in that The first preset thickness range is 4-20 nm.

4. The positive electrode material according to claim 1, characterized in that The first preset thickness range is 4-15 nm.

5. The positive electrode material according to claim 1, characterized in that The first preset thickness range is 5-10 nm.

6. The positive electrode material according to claim 1, characterized in that The second preset thickness range is 5-15 nm.

7. The positive electrode material according to claim 1, characterized in that The second preset thickness range is 6-12 nm.

8. The positive electrode material according to claim 1, characterized in that The second preset thickness range is 6-8 nm.

9. A method for preparing a positive electrode material for a lithium battery, for preparing the positive electrode material as claimed in any one of claims 1 to 8, characterized in that: The method comprises: Adding lithium acetate and anhydrous ethanol and tantalum ethoxide and anhydrous ethanol into a first container and a second container respectively, wherein the mass ratio of the tantalum ethoxide to the lithium acetate is within a preset ratio range; dropping the solution in the second container into the solution in the first container to form a mixed solution; Adding lithium cobalt oxide to the mixed solution, stirring and drying the mixed solution to form a dried product; The dried product is calcined to obtain the positive electrode material, and the calcination process adopts a preset temperature curve.

10. The preparation method according to claim 9, characterized in that: The preset temperature curve includes at least a temperature increase phase and a temperature decrease phase, and the temperature increase phase is substantially symmetrical to the temperature decrease phase.

Citation Information

Patent Citations

  • Modified multi-element precursor of lithium battery positive electrode material and preparation method of modified multi-element precursor

    CN107359346A

  • Solid oxygen layer-coated lithium cathode material with layered structure as well as preparation and detection methods of solid oxygen layer-coated lithium cathode material

    CN112038636A

  • Positive electrode material and preparation method and application thereof

    CN115000391A

  • High-nickel ternary positive electrode material, preparation method thereof and battery

    CN115043444A

  • Layered ordered and disordered core-shell structure lithium ion battery positive electrode material as well as preparation method and application thereof

    CN115084466A